Pendampingan Sertifikasi Halal pada Produk Kopi Khas Lombok di PT Beriuk Pacu Jaya - Putri, Destiana Adinda; Maharani, Andika Ellena Saufika Hakim; Meikapasa, Ni Wayan Putu; Arzani, Lalu Danu Prima; Naufali, Muhammad Nizhar; Adhamatika, Adhima (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Halal certification is an effort to protect consumers from consuming non-halal food by providing halal labels on packaging of product. The halal label is one of the requirement that influences decision making by consumers who want to buy the food products especially in Indonesia, one of the country with a high Muslim population. The Community Service Program (PKM) is implemented at coffee processing business actors with the trademark D'Bajangs produced by PT. Beruk Pacu Jaya located in Central Lombok.  The purpose of this activity is to increase the knowledge regarding the importance of Halal Certificatio for Small Micro Enterprise (UMK) and obtain the Halal Certificate. The method used in this activity is the lecture method, discussion and work instruction exercises. The results of this activity were increasing knowledge of the halal quality assurance system and understanding that halal certification is very important for its products. So that public trust in UMK products increases thereby increasing sales. As well as overseeing UMKM PT. Beriuk Pacu Jaya to obtain halal certification for typical Lombok coffee products with the trademark D'Bajangs in the SEHATI22 program initiated by BPJPH.